Perovskite Metal–Oxide–Semiconductor Structures for Interface Characterization. Issue 20 (27th September 2021) - Cunha, José M. V.; Barreiros, M. Alexandra; Curado, Marco A.; Lopes, Tomás S.; Oliveira, Kevin; Oliveira, António J. N.; Barbosa, João R. S.; Vilanova, António; Brites, Maria João; Mascarenhas, João; Flandre, Denis; Silva, Ana G.; et al.
Abstract: Perovskite solar cells (PSCs) are one of the most promising photovoltaic technologies. Amongst several challenges, developing and optimizing efficient electron transport layers that can be up‐scaled still remains a massive task. Admittance measurements on metal–oxide–semiconductor (MOS) devices allow to better understand the optoelectronic properties of the interface between perovskite and the charge carrier transport layer. This work discloses a new pathway for a fundamental characterization of the oxide/semiconductor interface in PSCs. Inverted MOS structures, that is, glass/fluorine‐doped tin oxide/tin oxide (SnO2 )/perovskite are fabricated and characterized allowing to perform a comparative study on the optoelectronic characteristics of the interface between the perovskite and sputtered SnO2 . Admittance measurements allow to assess the interface fixed oxide charges ( Qf ) and interface traps density ( Dit ), which are extremely relevant parameters that define interface properties of extraction layers. It is concluded that a 30 nm thick SnO2 layer without annealing presents an additional recombination mechanism compared to the other studied layers, and a 20 nm thick SnO2 layer without annealing presents the highest positive Qf values. Thus, an effective method is shown for the characterization of the charge carrier transport layer/perovskite interface using the analysis performed on perovskite‐based inverted MOS devices. Abstract : A new pathway to characterize the charge carrier transport layer/perovskite interface is shown through the use of inverted metal–oxide–semiconductor (MOS) devices. Admittance measurements performed on the MOS devices allow for the study of important optoelectronic properties of the charge carrier transport layer/perovskite interface, which will help to further improve perovskite solar cells.